ANALISIS KELENGKAPAN PENGISIAN SURAT BUKTI PELAYANAN KESEHATAN PASIEN RAWAT JALAN GUNA MENUNJANG PROSES KLAIM DI RSUP DR HASAN SADIKIN BANDUNG - Rizqy Dimas Monica (Jurnal TEDC, 2020)
Based on the results of the preliminary study conducted by the author in RSUP Dr Hasan Sadikin Bandung There are several issues of claim, one of which is the receipt of the letter of health care. The incompleteness of the letter of Health service evidence during January is 145 files. This method of research uses a descriptive research method with a quantitative approach. Observation data collection techniques, interviews, documentation studies. Research instruments use interview guidelines and stationery. The results of the author's research, that the central General Hospital Dr. Hasan Sadikin Bandung in the outpatient service unit there are 145 files of incomplete health service evidence and even some do not contain, the absence is in the signature and the name of the doctor also the patient, and there is no diagnostic writing on the sheet. Therefore, the medical record officer is impeded in the process of recording the diagnosis and data input in the INA-CBGs, because it must return the SCPC to the relevant party to be filled and equipped first before finally returned to the medical officer to do the claim. So that the process of claim is not yet running optimally.